Pathogenesis of Hendra and Nipah virus infection in humans - Escaffre, Olivier; Borisevich, Viktoriya; Rockx, Barry (Journal of infection in developing countries, 2013)
Hendra virus (HeV) and Nipah virus (NiV) are emerging zoonotic viruses that cause severe and often lethal respiratory illness and encephalitis in humans. Henipaviruses can infect a wide range of species and human-to-human transmission has been observed for NiV. While the exact route of transmission in humans is not known, experimental infection in different animal species suggests that infection can be efficiently initiated after respiratory challenge. The limited data on histopathological changes in fatal human cases of HeV and NiV suggest that endothelial cells are an important target during the terminal stage of infection; however, it is unknown where these viruses initially establish infection and how the virus disseminates from the respiratory tract to the central nervous system and other organs. Here we review the current concepts in henipavirus pathogenesis in humans.